21st Century Skills In Educational Standards For Lower Secondary Education In Slovakia - Haviar, Miroslav; Guffová, Daniela; Sisáková-Chovanová, Andrea (Norma, 2022)
The aim of this theoretical study is to identify the 21st century skills in the curricular documents for lower secondary education in Slovakia, and to analyse the overlap between the 21st century skills and aims of national educational standards for lower secondary education (ISCED 2) in Slovakia. The main method of the study is document analysis. The analysis shows that the Slovak educational standards are primarily focused on the development of knowledge and cognitive skills. Significantly less represented is development of interpersonal and intrapersonal skills. The results show that there are overall not sufficiently many references to the 21st century skills within the educational standards. This yields a crucial problem, as majority of Slovak teachers still consider the educational standards to be the basic part of curriculum. In spite of certain natural limitations, the study provides new information on the insufficient representation of the 21st century skills in the educational standards in Slovakia.
Keywords: educational standards; document analysis; lower secondary education; 21st century skills